Petrogenesis and tectonic significance of the middle Neoproterozoic highly fractionated A-type granite in the South Qinling Block - Qiu Xiaofei, Qiu Xiaofei; Xu Qiong, Xu Qiong; Jiang Tuo, Jiang Tuo; Lu Shansong, Lu Shansong; Zhao Long, Zhao Long (Geological magazine, 2021)
The South Qinling block, a segment of the Yangtze craton involved in the Qinling-Dabie orogen, is critical for understanding the tectonic evolution of eastern China. However, the tectonic setting of the South Qinling block and the northern margin of the Yangtze block during middle Neoproterozoic time has long been the subject of debate, with two distinctly different models (continental rift or volcanic arc) proposed. Here, a comprehensive study of zircon U-Pb geochronology and geochemistry has been carried out on the Chengwan granitic pluton from the Suizao terrane in the South Qinling block. The granites are monzogranite and syenogranite in lithology, and are mainly composed of potash feldspar, quartz, plagioclase and biotite. This suite has long been regarded as a Palaeozoic magmatic pluton, but zircon U-Pb ages of 809 ± 9 Ma and 816 ± 4 Ma are obtained in this study. The granites are metaluminous to strongly peraluminous with high alkali contents, and exhibit highly fractionated features, including high SiO2, low Zr/Hf ratios, rare earth element tetrad effects and enrichment of K and Rb. They show Hf-Nd isotopic decoupling, which may be genetically related to their petrogenetic process. Based on the geochemical features and the positive εHf(t) values of the zircons, it is indicated that the granites may have been derived from partial melting of juvenile tonalitic rocks by biotite breakdown under fluid-absent conditions. The Chengwan granite geochemically belongs to the A2-subtype granites, suggesting that it might have formed in a post-orogenic tectonic setting. The highly fractionated A-type granite in this study may represent extensional collapse shortly after the collisional events in the South Qinling block, and thus indicate a tectonic regime switch, from compression to extension, as early as middle Neoproterozoic time. Integrating our new data with documented magmatic, metamorphic and sedimentary events during middle Neoproterozoic time in the region may support a continental rift model, and argues against arc models.